From Micro to Macro: The Combination of Consciousness - Young, Asa; Robbins, Isabella; Shelat, Shivang (Frontiers in Psychology, 2022)
Crick and Koch’s 1990 “neurobiological theory of consciousness” sparked the race for the physical correlates of subjective experience. 30 years later, cognitive sciences trend toward consideration of the brain’s electromagnetic field as the primary seat of consciousness, the “to be” of the individual. Recent advancements in laboratory tools have preceded an influx of studies reporting a synchronization between the neuronally generated EM fields of interacting individuals. An embodied and enactive neuroscientific approach has gained traction in the wake of these findings wherein consciousness and cognition are theorized to be regulated and distributed beyond the individual. We approach this frontier to extend the implications of person-to-person synchrony to propose a process of combination whereby coupled individual agents merge into a hierarchical cognitive system to which they are subsidiary. Such is to say, the complex mammalian consciousness humans possess may not be the tip of the iceberg, but another step in a succeeding staircase. To this end, the axioms and conjectures of General Resonance Theory are utilized to describe this phenomenon of interpersonal resonant combination. Our proposal describes a coupled system of spatially distributed EM fields that are synchronized through recurrent, entraining behavioral interactions. The system, having achieved sufficient synchronization, enjoys an optimization of information flow that alters the conscious states of its merging agents and enhances group performance capabilities. In the race for the neurobiological correlates of subjective experience, we attempt the first steps in the journey toward defining the physical basis of “group consciousness.” The establishment of a concrete account of the combination of consciousness at a scale superseding individual human consciousness remains speculation, but our suggested approach provides a framework for empirical testing of these possibilities.